2014
DOI: 10.1016/j.cub.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

An Assay for Clogging the Ciliary Pore Complex Distinguishes Mechanisms of Cytosolic and Membrane Protein Entry

Abstract: Summary As a cellular organelle, the cilium contains a unique protein composition [1, 2]. Entry of both membrane [3–5] and cytosolic components [6–8] is tightly regulated by gating mechanisms at the cilium base, however, the mechanistic details of ciliary gating are largely unknown. We previously proposed that entry of cytosolic components is regulated by mechanisms similar to those of nuclear transport and is dependent on nucleoporins (NUPs) which comprise a ciliary pore complex (CPC) [6, 9]. To investigate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 46 publications
5
72
0
Order By: Relevance
“…However, this result was questioned in a recent study where ciliary SMO localization was found to be unaffected by simultaneous loss of b-arrestins 1 and 2 [53]. Further, single-molecule studies have indicated that SMO is translocated laterally from the plasma membrane into the ciliary compartment and, once inside the cilium, it primarily moves by diffusion and not IFT [22][23][24][25]. Similarly, two separate studies in Chlamydomonas have shown that specific membrane proteins can accumulate in the cilia of that organism independently of IFT [26,54].…”
Section: Intraflagellar Transport and Trafficking Within Ciliamentioning
confidence: 83%
See 1 more Smart Citation
“…However, this result was questioned in a recent study where ciliary SMO localization was found to be unaffected by simultaneous loss of b-arrestins 1 and 2 [53]. Further, single-molecule studies have indicated that SMO is translocated laterally from the plasma membrane into the ciliary compartment and, once inside the cilium, it primarily moves by diffusion and not IFT [22][23][24][25]. Similarly, two separate studies in Chlamydomonas have shown that specific membrane proteins can accumulate in the cilia of that organism independently of IFT [26,54].…”
Section: Intraflagellar Transport and Trafficking Within Ciliamentioning
confidence: 83%
“…Studies in multiple organisms have shown that ciliary assembly and maintenance rely on the vesicular transport of lipids and proteins from the trans-Golgi network (TGN) and recycling endosomes to the mother centriole/basal body, where vesicles are exocytosed and lipids and proteins are incorporated into the growing ciliary membrane [21]. Some ciliary membrane proteins, such as SMO of the Shh signaling pathway, may also enter the ciliary compartment by lateral transport or diffusion from the plasma membrane [22][23][24][25] ( Figure 1A). The pathways controlling vesicle and membrane protein trafficking to the cilium are complex and not fully understood.…”
Section: Targeting Of Vesicles To the Ciliary Basementioning
confidence: 99%
“…After docking, the proposed ciliary pore complex (CPC), possibly positioned at inter-fiber space of TFs, facilitates the import of assembled IFT particles. The molecular identities of the CPC remain mysterious, and molecular evidence supports [40, 51, 52] or challenges [42] the similarity of the CPC and NPC. It is worth determining if this active transport mechanism applies to other non-IFT ciliary proteins, how the CPC recognizes the cilia-targeting signal of ciliary proteins, and what is the functional and structural relationship among the CPC, TFs, and the TZ.…”
Section: Tfs Diffusion Barrier and The Ciliary Gatementioning
confidence: 99%
“…Many GFP-tagged nucleoporins localize to the base of the cilium, and introduction of inhibitors of NPC diffusion perturb the size-exclusion permeability barrier at the base of the cilium (Kee et al, 2012). Moreover, forced dimerization of Nup62 perturbs the directional trafficking of cytosolic proteins into the cilium, but has no effect on membrane proteins (Takao et al, 2014). Studies by other groups have shown functional roles for the nucleoporins Nup62 and Nup188 at the centrosome, which contributes its mother centriole to form the ciliary basal body (Hashizume et al, 2013;Itoh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that nucleoporins localize to the base of the cilium to form a complex that fulfills a role similar to that of the NPC, possessing activity as both a diffusion barrier and a regulator of directional import into the cilium (Kee et al, 2012;Takao et al, 2014). Many GFP-tagged nucleoporins localize to the base of the cilium, and introduction of inhibitors of NPC diffusion perturb the size-exclusion permeability barrier at the base of the cilium (Kee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%